The Credibility Mechanism: Modelling the Mediating Effect of Blockchain-Enabled Transparency on Sustainable Revenue Premium in Hotel Food & Beverage Supply Chains - Putranto, Diyan; Halawa, Fransiscus Amonio; Widodo, Rintis Eko; Setiawan, Fahmi; Ajizi , Budi Nurhamdani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The competitive hospitality sector faces a growing credibility crisis, where rising consumer skepticism regarding